LIVER TRANSPLANTATION IN JEHOVAH'S WITNESSES PATIENTS IN A CENTER OF NORTHEASTERN BRAZIL - GARCIA,José Huygens Parente (2013)
Context Liver transplantation has been accepted as a therapeutic option for patients with end-stage liver disease and acute liver failure. Currently, Brazil has a well-established public organ transplant program, performing 7,425 solid organs transplants in 2012 alone, among which 1,595 were liver transplants. Jehovah's Witnesses report 7,6 million members worldwide. For religious reasons they refuse transfusion of whole blood or its primary components (red cells, fresh frozen plasma, platelets). Objective This study aims to present the results obtained with Jehovah's Witnesses patients by a liver transplantation service. Method We conducted a retrospective review of medical records from Jehovah's Witnesses patients (n = 4) who underwent orthotopic liver transplantation from September 2009 to September 2011 at the Walter Cantídio University Hospital of the Federal University of Ceará, Fortaleza, CE, Brazil. Coagulation parameters such as Hemoglobin, Hematocrit, Platelets, INR were evaluated during the preoperative, immediate postoperative, postoperative day (POD) 7 and POD 30. Results Coagulation parameters were expressed as means: hematocrit, 35.07% ± 6.65%, 24.6% ± 4.74%, 19.85% ± 2.10%, 31.85% ± 5.99%; hemoglobin, 12.57 g/dL ± 2.22, 8.92 g/dL ± 1.75, 6.92 g/dL ± 0.58, 11.17 g/dL ± 0.9; platelets, 160,975 mm 3 ± 148000, 128,000 mm 3 ± 34836, 65,000 mm 3 ± 33496, 234,250 mm 3 ± 287003 and INR, 143 ± 0.10, 2.4 ± 0.34, 1.24 ± 0.10, 1.14 ± 0.09. Conclusion Liver transplantation can successfully be performed in Jehovah's Witnesses patient population provided that: 1) the medical team has extensive expertise in that field, 2) the patient has an adequate level of hematologic factors preoperatively, and 3) there is availability of specialized equipment such as cell saver to minimize blood loss and thus avoid transfusion requirements.